1997
DOI: 10.1086/514115
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Humanized Monoclonal Antibody (MEDI‐493) with Potent In Vitro and In Vivo Activity against Respiratory Syncytial Virus

Abstract: Neutralizing polyclonal antibody to respiratory syncytial virus (RSV) has been shown to be an effective prophylactic agent when administered intravenously in high-risk infants. This study describes the generation of a humanized monoclonal antibody, MEDI-493, that recognizes a conserved neutralizing epitope on the F glycoprotein of RSV. The affinity of MEDI-493 was found to be equal to or slightly better than an isotype-matched chimeric derivative of the parent antibody. In plaque reduction, microneutralization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
425
1
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(436 citation statements)
references
References 51 publications
3
425
1
7
Order By: Relevance
“…2A). Variants 19,21,22,24, and 25 consistently exhibited a moderate, although significant enhancement in CDC activity on various cell types tested (Fig. 3, C and D) when compared with their wild-type counterpart (12G3H11).…”
Section: Cdc Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…2A). Variants 19,21,22,24, and 25 consistently exhibited a moderate, although significant enhancement in CDC activity on various cell types tested (Fig. 3, C and D) when compared with their wild-type counterpart (12G3H11).…”
Section: Cdc Activitymentioning
confidence: 91%
“…The variable light and variable heavy genes of mAb 12G3H11 were individually cloned into mammalian expression vectors encoding a human CMV major immediate early enhancer, promoter, and 5Ј-untranslated region (20). In this system, a human ␥1 chain is secreted along with a human chain (21).…”
Section: General Description Of the Test Ab And Expression Vectorsmentioning
confidence: 99%
“…Indeed, some practice guidelines have suggested that ribavirin has comparatively better efficacy in the immunosuppressed population. 27 A humanized monoclonal antibody to the F protein of RSV (MEDI-493, palivizumab, Synagis) 28 became available after this protocol closed, and has a similar RSV preventative effect as RSV-IGIV for its indicated use. 29 This monoclonal antibody has also been shown to have an antiviral treatment effect in immunocompetent infants: RSV concentrations in palivizumab-treated patients dropped by 1.7 log at 24 h and 2.5 log at 48 h after a single intravenous 15 mg/kg dose, as compared to a 0.6 log (P = 0.004) and a 1.0 log (P = 0.012) drop in the placebo group at the same time points.…”
Section: Tablementioning
confidence: 99%
“…17,18 Recently, the RSV F nanoparticles produced in insect cells were reported to be safe in healthy individuals and young women of childbearing age in phase I and II clinical trials. 19,20 Protection was reported without causing RSV disease by immunization of mice with mixed F VLP and G VLP (FG VLP) vaccines with DNA plasmids expressing F proteins as evidenced by clearing lung viral loads and preventing pulmonary inflammation.…”
Section: Discussionmentioning
confidence: 99%